Defects and Dopants in Silicon Nanowires Produced by Metal-Assisted Chemical Etching. (1st January 2016) - Fanciulli, M.; Belli, M.; Paleari, S.; Lamperti, A.; Sironi, M.; Pizio, A.
Abstract : The current status of the investigation of defects in silicon nanowires and at the interface between Si and its oxide in 1D nanostructures is reviewed and discussed. The paper concentrates on nanowires produced by metal assisted chemical etching. The role of defects at the interface between the semiconductor and its oxide and of hydrogen in passivating donor atoms is addressed.